THU0067 CR6086, a Selective Antagonist at the EP4 Prostanoid Receptor, Improves or Resolves Disease Features in a Mouse Model of Rheumatoid Arthritis. (9th June 2015) - Chiusaroli, R.; Cavagnoli, R.; Letari, O.; Lanza, M.; Caselli, G.; Rovati, L.
Abstract : Background: Recent studies highlight the role of the EP4 prostanoid receptor in promoting autoimmune inflammation via T helper cells, Th1 and Th17. Objectives: Aim of the present studies was to test CR6086, an EP4 selective antagonist, in a widely recognized animal model for rheumatoid arthritis, i.e. the collagen II-induced arthritis (CIA) model in the DBA/1 mouse. The effect of CR6086 was studied in comparison to naproxen to distinguish an immunomodulatory activity from that of a classical NSAID. Methods: 70 DBA/1 male mice were immunized with collagen type II in CFA or were injected with incomplete Freund's adjuvant (sham group, n=10). Upon arthritis onset, animals were assigned to experimental groups, arthritis clinical score was assigned and edema measured. Treatment groups (n=8-9) were: vehicle; CR6086 30 and 60 mg/kg/o.a.d.; naproxen 60 mg/kg o.a.d. Edema measurement was performed every day before treatment, and all animals were blindly scored for clinical signs of arthritis. After 10 days of treatment, the animals were sacrificed and bled for serum tests. Hindpaw joints were blindly scored for histological features: edema; synovial hyperplasia; inflammatory cell infiltrate; cartilage damage; bone erosion; periosteal osteogenesis. Statistical analyses were performed with ANOVA followed by Dunn's or Holm-Sidak's tests comparing all treatment groups vs. vehicle. Results: Within 3 days of treatment, edema was significantly reduced in CR6086 30 and 60 mg/kg treatment groups compared to vehicle (vehicle, 3.6±0.67; CR6086 30 mg/kg: 2.65±0.56, p<0.05 vs. control; CR6086 60 mg/kg: 2.23±0.35, p<0.05 vs. control; naproxen, 3.00±0.49, n.s). In the CR6086 60 mg/kg group, edema was completely abated after 10 days of treatment while CR6086 30 mg/kg significantly reduced edema. Administration of naproxen did not show a significant effect on edema development (vehicle, 3.74±0.69; CR6086 30 mg/kg: 2.69±0.46, p<0.05 vs. control; CR6086 60 mg/kg: 2.19±0.5, p<0.05 vs. control; naproxen, 3.03±0.64, n.s.). CR6086 also demonstrated very potent, dose-dependent activity in reducing severity of arthritis clinical score. Administration of naproxen did not show a significant effect on this parameter (vehicle, 2.63±1; CR6086 30 mg/kg: 1.45±1.12, n.s.; CR6086 60 mg/kg: 0.36±0.94, p<0.05 vs. control; naproxen, 2.07±1.43, n.s.). All histological features of arthritis were dose-dependently, profoundly and significantly ameliorated following treatment with CR6086. A non significant trend in the same features was associated to administration of naproxen (Fig. 1 ). Circulating IL-6 levels were decreased by CR6086 treatment but not by naproxen (sham 28.9±5; vehicle, 290.15±96.42; CR6086 30 mg/kg: 256.66±59, n.s.; CR6086 60 mg/kg: 56.7±21.2, p<0.05 vs. control; naproxen, 251.4±50.2, n.s. Conclusions: In a widely recognized animal model for rheumatoid arthritis, CR6086 demonstrated very good efficacy in all parameters examined, including edema, clinical arthritis score, and histological features, whereas naproxen only showed very mild, non-significant activity at best. The effect of CR6086 on circulating IL-6 supports a putative immunomodulatory activity. CR6086 is now in clinical phase I. Disclosure of Interest: R. Chiusaroli Employee of: Rottapharm Biotech Srl, R. Cavagnoli Employee of: Rottapharm Biotech Srl, O. Letari Employee of: Rottapharm Biotech Srl, M. Lanza Employee of: Rottapharm Biotech Srl, G. Caselli Employee of: Rottapharm Biotech Srl, L. Rovati Shareholder of: Rottapharm Biotech Srl, Employee of: Rottapharm Biotech Srl